The book of Genesis ; v. 2 - Aalders, Gerhard Charles, 1880-; Heynen, William (Grand Rapids, MI Zondervan, 1981)
Contents : v. 2 : Commentary on Genesis chapter 18-50.
Originally published in Dutch as Het boek Genesis
Keywords: Bible. O.T. Genesis XVIII-L -- commentaries